Consequence of E-Hrm Practices in Employee Retention for Sustainable Growth among Corporate Hospitals - Dr. K. Chandrasekar, N. Sathiyendran (International Journal of Advanced Science and Technology, 2019)
HRM is that the (planning, implementation and) application of knowledge technology for each networking and supporting a minimum of two individual or collective actors in their shared acting of unit of time activities. There are three sorts of E-HRM. These are portrayed separately as Operational, Relational and Transformational. Operational E-HRM is worried about regulatory capacities - finance and representative individual information for instance Lastly e-HRM makes institutionalization, and with institutionalized techniques this can guarantee that an association stays consistent with HR necessities, therefore additionally guaranteeing progressively exact basic leadership. Keyword:. HRM, E-HRM , Operational E-HRM, Lastly e-HRM,